Psychological Studies in Cyberlaw: An Interdisciplinary Exploration - Zaroh, Angelina Septiani; Purwaningsih, Sri Budi; Hasan, Rizqi (Proceedings of The ICECRS, 2023)
This data article examines the intersection of Cyberlaw, Psychological Studies, and Law through a comprehensive dataset sourced from lens.org. Focusing on Journal Articles from 1950 to 2020, the study reveals a notable surge in publications from 2016, underscoring the growing significance of this interdisciplinary field. Top institutions like University of Nebraska-Lincoln, University of Cambridge, and Queensland University of Technology lead in publishing Psychological studies in Cyberlaw. Key authors, including Gerald Young and Richard Rogers, have made substantial contributions. Springer Nature and the American Psychological Association stand out as influential publishers in disseminating this knowledge. The dataset unveils trends, prolific authors, active institutions, and influential journals, serving as an invaluable resource for researchers investigating this convergence. Highlights: Surging Publications: Noteworthy increase post-2016 highlights field relevance. Institutional Leaders: Top universities drive Psychological studies in Cyberlaw. Author Contributions: Notable authors like Gerald Young shape the field's discourse. Keywords: Cyberlaw, Psychological Studies, Law, Interdisciplinary Research, Scholarly Publications